Sustainable Leadership among Managers of Private Secondary Schools in Jeddah Governorate and its Relationship to Teachers’ Innovative Work Behavior (The International Journal of Educational Sciences and Arts, 2023)
The aim of this study is  to identify the scope of practicing  sustainable leadership by managers of private secondary schools in Jeddah Governorate, to determine to what extent the availability of innovative work behavior among teachers, to classify the correlation between the practice of principals of private secondary schools in Jeddah Governorate for sustainable leadership and innovative work behavior of teachers, also to detect the differences Statistically significant between the averages of teachers' responses about their estimates of  practicing  sustainable leadership by principals of their schools, which is attributed to the variables (gender, years of experience), and revealing statistically significant differences between the arithmetic mean  of teachers' responses about their estimates of their innovative work behaviors; Which is attributed to the difference (gender, years of experience). A quantitative approach (survey and correlation) is used to achieve the objectives of the study and to collect data. Researchers used the sustainable leadership scale prepared by Hargreaves & Fink (Hargreaves & Fink 2012), translated it, and based on its codification and arbitration by Al-Khamisa (2022) which he translated and based on codifying Al-Qarni (2020). The study community consisted of private school teachers at the secondary stage, whose number was (1589), the research sample was chosen using the appropriate random sample method (opportunity sample), whose number was (336) with a percentage of (21, 1) from the study population.According to findings of the study school principals contribute to practice sustainable leadership with a (high) level and all dimensions of sustainable leadership came with a high degree of practicing among school principals. The study also found that innovative work behavior is available to teachers with a (high) degree from their perspectives. In addition, it was found that there is a high-value and statistically significant direct correlation relationship at the level of significance (0.01) between the practice of sustainable leadership by school principals and the innovative work behavior of teachers.Moreover, the results show that there were no statistically significant differences in their appreciation of the practice of sustainable leadership by their school principals according to the different years of experience, while the study illustrated that there were statistically significant differences in their appreciation of the practice of sustainable leadership by their school principals according to gender. In contrast, the study demonstrates that there were no significant differences statistics between the averages of teachers' responses about their appreciation for their innovative work behavior according to the variables (gender and years of experience).The research recommends the necessity of consolidating the concept of sustainable leadership among school principals through programs and training packages, holding seminars and conferences that promote this concept and entrenching it among educators, building specific initiatives aiming at promoting innovative work behavior of teachers, and establishing activities and events that ensure the sustainability of these practices in work environments scholastic. The current study suggests some future studies related to the study variables.
Keywords: Sustainable Leadership; Managers of Private Secondary Schools; Teachers’ Innovative Work Behavior